2018
DOI: 10.1080/09553002.2018.1511931
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mucus thickness and goblet cell hyperplasia on microdosimetric quantities characterizing the bronchial epithelium upon radon exposure

Abstract: Purpose: The most exposed tissue upon radon exposure is the bronchial epithelium where goblet cells serve as responsive and adaptable front-line defenders. They can rapidly produce a vast amount of mucus, and can change in number, in response to airway insults. The objective of the present study is to quantify the effects of mucus discharge and goblet cell hyperplasia on the microscopic dose consequences of macroscopic radon exposures. Methods: For this purpose, computational models of the bronchial epithelium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 30 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Results show that average tissue dose, average hit number and dose of basal cells decrease by the increase of the measure of both basal and goblet cell hyperplasia [9,10]. Hit and dose distributions reveal that the induction of hyperplasia may result in a basal cell pool which is shielded from alpha-particles in particular in case of goblet cell hyperplasia where both mucus thickening and the additional number of goblet cells decrease cellular burdens.…”
Section: Resultsmentioning
confidence: 97%
“…Results show that average tissue dose, average hit number and dose of basal cells decrease by the increase of the measure of both basal and goblet cell hyperplasia [9,10]. Hit and dose distributions reveal that the induction of hyperplasia may result in a basal cell pool which is shielded from alpha-particles in particular in case of goblet cell hyperplasia where both mucus thickening and the additional number of goblet cells decrease cellular burdens.…”
Section: Resultsmentioning
confidence: 97%
“…The conjecture that hyperplasia occurs in the highly exposed carinal regions of the bronchial airways is supported by experimental (Rogers 2003) and histological findings (Auerbach et al 1961). Simulations indicated that an increase in progenitor cell number reduces not only the cell division rate for a given exposure rate, but also the microscopic energy deposition in the tissue (Madas 2016;Madas and Drozsdik 2018). As the number of progenitor cells increases, the bronchial epithelium tissue becomes thicker, thereby increasing the average distance between alpha decay sites and progenitor cells, and hence reducing the mean number of cellular hits.…”
Section: From Cellular Microdosimetry To the Tissue And Organ Levelmentioning
confidence: 92%
“…While the increase of the cell division rate and the induction of DNA damage exhibit a synergistic response, results indicated that radon progeny alpha particles primarily cause mutations in the epithelium via the induced replacement of killed cells . Madas (2016), Madas and Drozsdik (2018), and Drozsdik and Madas (2019) also explored the role of hyperplasia on radon-induced lung cancer risk. The conjecture that hyperplasia occurs in the highly exposed carinal regions of the bronchial airways is supported by experimental (Rogers 2003) and histological findings (Auerbach et al 1961).…”
Section: From Cellular Microdosimetry To the Tissue And Organ Levelmentioning
confidence: 99%
“…One of the mechanisms reducing the cell division rate is the increase of progenitor cell number, as less divisions are required if there is a larger pool of cells capable of division. Based on histological (Auerbach et al 1961 ) and experimental evidence (McDowell et al 1979 ) as well as considerations in mathematical biology (Lander et al 2009 ), it was proposed that chronically high exposure to radon progeny can induce basal and goblet cell hyperplasia in the deposition hot spots (Madas and Balásházy 2011 ; Madas 2016b ; Madas and Drozsdik 2018 ).…”
Section: Models Linking Effects At Different Levels Of Biological Org...mentioning
confidence: 99%